The context of relative equality: Comparing educational gradients in the gendered division of labor in three liberal markets - Lynn Prince Cooke; Liana C. Sayer (Luxembourg Income Study (LIS), 2012)
We compare the educational gradient in employment, housework and child care in Australia, the United Kingdom and the United States using recent LIS and Multinational Time Use data. All three countries have above-average aggregate income inequality, but it is least in Australia and greatest in the United States. The greater aggregate income equality in Australia narrows educational differences across women as well as men, and in turn the gender differences in employment hours at each level of education. The compromise for this greater equality is a greater gendered division of housework, but not child care. The UK and US aggregate income inequality allows highly-educated, particularly US women to reduce their housework time, but at a cost of longer total work hours for educated men and women, and greater educational differences across women. Thus aggregate income equality shapes relative gender equality in paid and unpaid work between women and men, and among women.
Keywords: 330; Bildungsniveau; Einkommensverteilung; Australien; Großbritannien; USA